Evaluation of the trade-off between variety, processing, and low-GI claim in ready-to-eat rice - Cabral, Diva (2024)
An increasing number of consumers demand healthier, more convenient, and sustainable food products, including rice, a staple worldwide. Food manufacturers have responded to this trend by considering food’s intrinsic and extrinsic aspects. This study evaluated the importance of variety, processing, and claims on willingness to try ready-to-eat rice (RTE-rice). It also analyses the influence of consumer attitudes on the importance of attributes and willingness to try. The results showed that processing significantly influenced willingness to try RTE-rice, revealing consumers’ greater preference for whole grain than milled rice with added bran. Claims had the least relevant importance. However, low glycaemic index had a positive impact, indicating its potential to influence consumer purchasing attitudes and promote healthier rice consumption. Additionally, three groups were created based on attitudinal factors. Naturalness-oriented and convenienceoriented groups were more likely to try RTE-rice. However, the reasons that motivate them may be different; this latter could be the ease of the service offered, while for the group focused on naturalness, they may have perceived through the ingredients and claimed that the product, despite being convenient, can bring benefits, thus perceiving them as natural.